The Role of Agricultural Extension Officers in Developing Farmer Groups: A Case Study in Sinjai District - Nurdin, Fadilah; Taslim, Andi Irga Satrawati; Qinayah, Mirnatul; Raisa, Daeva Mubarika (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to describe the role of agricultural extension officers in the development of the Pattiro Kondoe Farmer Group in Saharu Hamlet, Lamatti Riattang Village, Bulupoddo District, Sinjai Regency. Using a descriptive qualitative approach with the support of quantitative data through a Likert scale questionnaire, this study involved 18 active members of the farmer group who were purposively selected. Five main roles of extension workers were studied, including facilitator, innovator, motivator, dynamizer, and educator. The results showed that the roles of extension workers as innovators and facilitators scored the highest in the excellent category, followed by the other roles with good scores. Nevertheless, a number of barriers were found, such as limited field visits, farmers' dependence on external assistance, and low participation of certain members. These findings point to the importance of continued support for extension workers, strengthening of participatory mentoring models, and the need for more relevant agricultural technology training. This study recommends that agricultural policies in remote areas pay more attention to the sustainability of the role of extension workers in strengthening farmers' institutions independently.